Dosis Penggunaan Mikroorganisme Lokal (MOL) Ragi Tempe dan Isi Rumen untuk Pengomposan - Firdaus, F.; Purwanto, B. P.; Salundik, Salundik (Jurnal Ilmu Produksi dan Teknologi Hasil Peternakan, 2014)
The bioactivator was required to accelerate the composting process. Local micro-organism (LMO) tempe yeast and rumen content were an alternative of bioactivator that could be easily obtained and made. Bacterias and fungis in the tempe yeast and the rumen content could decomposed the organic matters. The objectives of this research  was to study: 1) growth media which good for both local micro-organism (LMO)  tempe yeast and rumen content and 2) optimal dose of LMOtempe yeast and rumen content for composting. Growth media used was soybean and rice bran, ands for level dosage using 1%, 2%, 3%. Variables observed were total colonied of bacteria, yeast, and mold. Compost quality includes the value of C-organic, Nitrogen, Phosphor and Kalium. Data analysis conducted by ANOVA by using completely randomized design factorial with two factor (LMO and dosage), and continued with Tukey test. The result showed the good media for LMO growth was soy bean which harvested at third day, whereas the best dosage to use is 3%.